2022
DOI: 10.1002/hep.32562
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress in liver diseases

Abstract: The endoplasmic reticulum (ER) is an intracellular organelle that fosters the correct folding of linear polypeptides and proteins, a process tightly governed by the ER‐resident enzymes and chaperones. Failure to shape the proper 3‐dimensional architecture of proteins culminates in the accumulation of misfolded or unfolded proteins within the ER, disturbs ER homeostasis, and leads to canonically defined ER stress. Recent studies have elucidated that cellular perturbations, such as lipotoxicity, can also lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
86
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 131 publications
(232 reference statements)
1
86
0
Order By: Relevance
“…Pediatric cholestatic liver diseases are the leading indication for pediatric liver transplantation and there are currently no effective medical therapies that reduce the need for liver transplantation. During cholestasis, high intrahepatic concentrations of bile acids increase ER stress and hepatocellular injury, and an effective UPR response is essential to restore cellular homeostasis 25 Inadequate activation or dysregulation of the IREα/XBP1 pathway of the UPR has been implicated in the pathogenesis of several liver diseases 23 . Puri et al demonstrated that decreased levels of XBP1s protein expression was associated with the development of steatohepatitis in adult patients, although, although there remains some conflicting data 8, 24, 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric cholestatic liver diseases are the leading indication for pediatric liver transplantation and there are currently no effective medical therapies that reduce the need for liver transplantation. During cholestasis, high intrahepatic concentrations of bile acids increase ER stress and hepatocellular injury, and an effective UPR response is essential to restore cellular homeostasis 25 Inadequate activation or dysregulation of the IREα/XBP1 pathway of the UPR has been implicated in the pathogenesis of several liver diseases 23 . Puri et al demonstrated that decreased levels of XBP1s protein expression was associated with the development of steatohepatitis in adult patients, although, although there remains some conflicting data 8, 24, 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group utilized a bile acid feeding model of cholestasis and bile acid toxicity to demonstrate that, compared to adult mice, young mice had decreased XBP1s downstream target activation, with a resultant enhanced susceptibility to bile acid induced liver injury and apoptosis [ 15 ]. Additionally, inadequate activation of the IREα/XBP1 pathway has been implicated in the pathogenesis of several adult liver diseases [ 24 ]. Puri et al demonstrated that decreased levels of XBP1s protein expression were associated with the development of steatohepatitis in adult patients, although there remains some conflicting data on UPR expression in other NAFLD/NASH studies [ 8 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is now abundantly clear that ER stress is associated with fatty liver disease in humans and mouse models thereof (3). It is also likely that ER stress contributes to disease pathogenesis, since mice with an impaired ability to respond to ER stress in the liver are sensitized to experimental insults that lead to liver injury including alcohol, western diets, and pharmacotoxins that target the liver (4). The pathways by which ER stress affects hepatic function and exacerbates liver injury are still being characterized.…”
Section: Introductionmentioning
confidence: 99%